Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 1995)
Table of Content Marie José Burki : Le tremblement de l’être by Daniel Kurjakovic Peter Hujar by Nan Goldin Vija Celmins Vija Celmins: Material Fictions by Nancy Princenthal Night, Sleep, Death, and the Stars by Jim Lewis Vija Celmins, A Conversation with Jeanne Silverthorne Vija Celmins’ Play of Imitation by Richard Shiff Andreas Gursky On the Melancholy of Vantage Points by Jean-Pierre Criqui Andreas Gursky, Painter of New Theaters of Action by Jacqueline Burckhardt Brasilia, Vanishing Points by Neville Wakefield How Familiar is it? by Collier Schorr Rirkrit Tiravanija Guess Who’s Coming to Dinner by Alexandre Melo Forget About the Ball and Get on with the Game by Liam Gillick & Rirkrit Tiravanija En route by Richard Flood & Rochelle Steiner Hans Danuser, Insert Micromegas by Lynne Cooke The Trap Slams Shut: Andreas Slominski by Noemi Smolik Jean Painlevé and Mark Dion by Jason Simon A Wordscape. On Mark Luyten by Luk Lambrecht Les Infos du Paradis by Liam Gillick and Douglas Gordon Transoceanexpress, Cumulus from Europe by Alexandre Melo Sense and Sentimentality, Cumulus from America by David Deitcher
DISTANCE The difference is conspicuous: Parkett has changed. We are looking forward to the future because the changes—only three issues a year, but more voluminous and with a sewn binding, instead of the previous four in an adhesive binding—offer a challenging opportunity to expand the playing potential of our instrument, Parkett. The extra month between issues corresponds to the proportional increase in the size; the additional pages (the new binding will make for easier reading and a more durable publication) allow us to explore new forms in which to juxtapose our collaboration artists. (editorial by publisher)
boek
Keywords: Celmins, Vija; Tiravanija, Rirkrit; Gursky,Andreas